2001
DOI: 10.1136/jms.8.4.204
|View full text |Cite
|
Sign up to set email alerts
|

Does mammographic screening and a negative result affect attitudes towards future breast screening?

Abstract: Objectives-To investigate the impact of an experience of a benign mammographic result on intention to seek medical help immediately in the case of breast abnormalities, and on intentions and thoughts about future participation in screening. Setting-The Dutch Breast Cancer Screening Programme for women aged 50-69. Methods-Subjects were women who were invited for an initial breast examination: 223 women filled out a questionnaire about 10 days before and about 6 weeks after their initial breast examination. To b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…The concept of CAD and the need for a trial in the screening programme are difficult to explain in lay terms within the confines of a participant information sheet so it is perhaps not surprising that even a simplified information sheet may have had little impact. This may indicate that women were not reading the information sheet 20 or that they had difficulty understanding the original and the simplified version. 24 In Coventry and Manchester, all women recruited into the study attended mobile screening units, an environment that is not ideal for recruitment due to logistical limitations of space, time and available staff.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of CAD and the need for a trial in the screening programme are difficult to explain in lay terms within the confines of a participant information sheet so it is perhaps not surprising that even a simplified information sheet may have had little impact. This may indicate that women were not reading the information sheet 20 or that they had difficulty understanding the original and the simplified version. 24 In Coventry and Manchester, all women recruited into the study attended mobile screening units, an environment that is not ideal for recruitment due to logistical limitations of space, time and available staff.…”
Section: Discussionmentioning
confidence: 99%
“…There are only few studies that evaluated the effect of negative mammography results (Drossaert et al, 2001). False-negative mammography results occur least among females 40-49 years old (1.0 per 1000 females per screening round) (Drossaert et al, 2001).…”
Section: False-negativesmentioning
confidence: 99%
“…False-negative mammography results occur least among females 40-49 years old (1.0 per 1000 females per screening round) (Drossaert et al, 2001). However, additional studies seem necessary to understand the rate and burden of false-negative mammography findings in these females.…”
Section: False-negativesmentioning
confidence: 99%
“…Of these studies, three used a prospective design, [222][223][224] with two of them also collecting baseline measures (prescreening). 222,224 The studies that investigated the effects of screening on future outcomes reported that receiving a false-positive result increased perception of susceptibility to breast cancer and led to increased GP visits, 222 and that reattendance rates at the next routine breast screening appointment were lower in the women with false-positive results than in women who received a normal result.…”
Section: Papers Published Since the Year 2000mentioning
confidence: 99%
“…222,224 The studies that investigated the effects of screening on future outcomes reported that receiving a false-positive result increased perception of susceptibility to breast cancer and led to increased GP visits, 222 and that reattendance rates at the next routine breast screening appointment were lower in the women with false-positive results than in women who received a normal result. 223 Reattendance at the next routine breast screening appointment was investigated in a further two papers, both focusing on women who received false-positive results.…”
Section: Papers Published Since the Year 2000mentioning
confidence: 99%